Multiuser secret key generation based on received signal - Aolin CAI; Liang JIN; Zhou ZHONG; Yangming LOU (网络与信息安全学报)
The secret key generation method based on channel characteristic provides a new way for communication security.But under the conditions of multiuser and slow fading,because of the slow channel parameter changing rate,using the secret key generation method above can result in a low secret key rate.To solve this problem,a multiuser secret key generation method based on the received signal was proposed.By distributing the random signals to different users using block diagonalization precoding,base station and user can extract the secret key from the received signal.The novel method could significantly increase the secret key rate of multiuser under the quasi-static channel and slow-fading channel,which is verified by simulations.